The Golden Horde between Governance and Religious Doctrine: Reflections on A.G. Yurchenko’s Duologue (Golden Horde: Between Yasa and Quran. Beginning of the Conflict. SPb: Evrazija, 2012; Khan Uzbek: Between Empire and Islam (structure of everyday life). Compendium Book. SPb.: Evrazija, 2013) » - Yu.V. Seleznev (Золотоордынское обозрение)
This article contains a review of two monographs by A.G. Yurchenko. In both monographs Yurchenko explores religious situation in the ulus of Jochi in the 13th–15thcenturies. The author of duologue analyzes the structure of everyday life in the Horde State during the 13th–14th centuries, reflecting the ratio of its religious and administrative bases. Yurchenko comes to a conclusion about the existence of a more complex structure of the Horde society in terms of the confessional and political structure of the ulus of Jochi. According to the arguments presented by Yurchenko, one can conclude that the complex social structure preserved even after the Uzbek’s adoption of Islam. At the same time, the imperial “vertical of power” based on nomadic tradition and corresponding rituals changed slowly and reluctantly. However, at the highest administrative level, among the Horde elite, belonging to the Muslim faith became mandatory, and only this affiliation allowed to occupy senior posts in the State. This status of religious doctrine within the political system can justifiably be called a State ideology or religion of the State. At the same time, aspects highlighted by Yurchenko (a model of nomadic State, where religious institutions are separated from the State, and sacral-religious, philosophical discourses of sources on the history of the Horde) deserves attention and further development. To understand the current of social processes within the ulus of Jochi during the 13th–15th centuries, to get closer to scientific knowledge of the real history of the Horde, one should critically deal with the sources and consider the Horde’s reality through the prism of ideologico-religious and philosophical doctrines of the time, especially, in the Middle Ages. This article provides additional arguments both in favor of conceptual constructions of the author and in their rebuttal as well. Author of the review finds it necessary to carefully and critically deal with information of medieval sources on the history of the Horde, taking into account conclusions proposed by Yurchenko.